Social policy - Bochel, Hugh M.; Daly, Guy (Routledge, 2020)
This thoroughly revised and expanded new edition provides a comprehensive introduction to contemporary social policy and addresses its historical, theoretical and contextual foundations as well as contemporary policy issues relating to health, education and welfare as well as the impact of Brexit. Divided into four sections, it opens with a survey of the socio-economic, political and governmental contexts within which social policy operates, before moving on to look at the historical development of the subject. The third section examines contemporary aspects of providing welfare, whilst the final part covers European and wider international developments"--